Accelerated enhanced Recovery following Minimally Invasive colorectal cancer surgery (RecoverMI): a study protocol for a novel randomised controlled trial. Issue 7 (20th July 2017) - Price, Brandee A; Bednarski, Brian K; You, Y Nancy; Manandhar, Meryna; Dean, E Michelle; Alawadi, Zeinab M; Bryce Speer, B; Gottumukkala, Vijaya; Weldon, Marla; Massey, Robert L; Wang, Xuemei; Qiao, Wei; et al.
Abstract : Introduction: Definitive treatment of localised colorectal cancer involves surgical resection of the primary tumour. Short-stay colectomies (eg, 23-hours) would have important implications for optimising the efficiency of inpatient care with reduced resource utilisation while improving the overall recovery experience with earlier return to normalcy. It could permit surgical treatment of colorectal cancer in a wider variety of settings, including hospital-based ambulatory surgery environments. While a few studies have shown that discharge within the first 24 hours after minimally invasive colectomy is possible, the safety, feasibility and patient acceptability of a protocol for short-stay colectomy for colorectal cancer have not previously been evaluated in a prospective randomised study. Moreover, given the potential for some patients to experience a delay in recovery of bowel function after colectomy, close outpatient monitoring may be necessary to ensure safe implementation. Methods and analysis: In order to address this gap, we propose a prospective randomised trial of accelerated enhanced Recover y following M inimally I nvasive colorectal cancer surgery ( RecoverMI ) that leverages the combination of minimally invasive surgery with enhanced recovery protocols and early coordinated outpatient remote televideo conferencing technology ( TeleRecovery ) to improve postoperative patien-provider communication, enhance postoperative treatment navigation and optimise postdischarge care. We hypothesise that RecoverMI can be safely incorporated into multidisciplinary practice to improve patient outcomes and reduce the overall 30-day duration of hospitalisation while preserving the quality of the patient experience. Ethics and dissemination: RecoverMI has received institutional review board approval and funding from the American Society of Colorectal Surgeons (ASCRS; LPG103). Results from RecoverMI will be published in a peer-reviewed publication and be used to inform a multisite trial. Trial registration number: NCT02613728; Pre-results.